Ulisse Aldrovandi’s Museo Naturale and its role in the development of natural history in the Europe of the XVI century - O. V. Chervonenko (History of science and technology, 2018)
Ulisse Aldrovandi was a famous Italian naturalist, the first full professor in the history of natural sciences, who made a large contribution into the establishment of museums and the science of natural history in Europe. The paper presents detailed information on Aldrovandi’s biography and the tangled path of formation of his scientific interests. A special attention is paid to the little known information on features of Aldrovandi’s natural history collections and unique museum, which were studied by the author personally in the University of Bologna, Italy in 2018. The museum, which was conceived and created by Aldrovandi, has been preserved practically unchanged with only insignificant losses. Collection catalogues, complied by the scientist and analysed by us, show Aldrovandi’s ambition to account, catalogue, and classify available natural items and other objects that, in his opinion, reflect the role of nature in humans’ life. A detailed survey of Aldrovandi’s illustrated multi-volume (400 volumes) encyclopedia, which was based on his collections, is presented in the paper. It is highlighted that, despite Aldrovandi’s progressive views and high level of education, naive interpretations with descriptions of fantastic creatures such as mermaids, sphinxes, dragons and others are given in his works along with scientific facts. Nevertheless, the scientist saw and noted the boundary between empiric investigation of the nature and its symbolic interpretation. Aldrovandi was the first scholar who involved a large deal of original and direct research into natural history and gathered a scientific collection of natural items. The majesty of his plan, the volume of his collections and scientific interests impressed the scientist’s contemporaries, who acclaimed Aldrovandi’s Museo Naturale as “the best cabinet of Europe and the largest micro cosmos of nature” in that time. It is emphasised that Aldrovandi’s natural history collection became part of the social and cultural context of the emergence of natural history as a scientific discipline. The extremely huge role of Aldrovandi’s museum in popularisation is also noted, since it proposed “wisdom” for the spread of scientific information in forms appropriate for sensation at that time.